Performance of STOP-BANG questionnaire as sleep apnoea screening tool and development of a novel pre-selection model in patients with atrial fibrillation - insights from the Virtual-SAFARI study. (19th May 2022) - Betz, K; Verhaert, DVM; Gawalko, M; Hermans, ANL; Van Der Velden, RMJ; Schotten, U; Vernooy, K; Hendriks, J; Linz, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Sleep-disordered breathing (SDB) is highly prevalent in patients with atrial fibrillation (AF) and its screening is recommended in this population. The STOP-BANG questionnaire is widely used as SDB screening tool, but the subjective assessment of some of its parameters might limit its validity to detect SDB in AF patients. Purpose: We assessed the performance of the STOP-BANG questionnaire to detect SDB with the use of a mobile health-based portable home sleep test given as reference in a cohort of AF patients. Moreover, we explored options to improve pre-selection for SDB screening in this cohort. Methods: Consecutive AF patients who were referred for AF catheter ablation in two AF outpatient clinics and without previous history of SDB and/or SDB screening, were included prospectively. Patients characteristics together with STOP-BANG questionnaire were assessed at baseline visitation. STOP-BANG scores of 3-4 and 5-8 were interpreted as intermediate and high risk for SDB, respectively. All patients were digitally referred to a virtual SDB management pathway, independent of STOP-BANG score. Patients received a portable home sleep test to detect SDB, which patients used for one night at home after instructions. Sleep recordings were accessed by sleep physicians via a secured cloud and sleep reports were discussed with patients and referring physicians. Apnoea-hypopnoea-indexes (AHI) of >=15 and of >= 30 were interpreted as moderate-to-severe and severe SDB, respectively. Results of the STOP-BANG and the home sleep test were compared and performance of the STOP-BANG questionnaire was assessed. Uni- and multivariable logistic regression analyses based on patient characteristics were used to construct a nomogram to improve pre-selection for SDB screening in this cohort. Results: A total of 156 patients (median age 65 years, 63.8% male) were included. According to results from the home sleep test, 53% of patients were diagnosed with moderate-to-severe SDB, including 16% with severe SDB. STOP-BANG questionnaire performed poorly with an area under the receiver operating characteristic curve (AUROC) of 0.661 and 0.684 in predicting moderate-to-severe and severe SDB, respectively. On multivariable logistic analysis, independent predictors for moderate-to-severe SDB were body-mass-index (BMI), age and apnoeas. A nomogram was built on this variables (Fig. 1), which performed good with an AUROC of 0.728 in predicting moderate-to-severe SDB. Conclusion: In a cohort of AF patients scheduled for AF catheter ablation, SDB was highly prevalent. STOP-BANG questionnaire had poor value for the prediction of moderate-to-severe and severe SDB compared to a systematical SDB screening via home sleep test. Using STOP-BANG questionnaire as a pre-selection tool might lead to frequently undetected and untreated SDB. Whether the nomogram based on our analyses improves pre-selection for SDB screening in AF patients will be validated in a future cohort.